Обробка і захист інформації в інформаційно-комунікаційних системах - Пономарьов, А. К.; Штих, І. А. (ХНУРЕ, 2018)
The widespread use of computer technologies in automated information processing and management systems has exacerbated the problem of protecting information circulating in computer systems from unauthorized access. The pro-tection of information in computer systems has a number of specific features re-lated to the fact that information is not rigidly connected with the medium, can be copied easily and quickly and transmitted through communication channels. A very large number of threats of information are known, which can be realized both by external violators and by internal violators.
Keywords: захист інформації; комунікаційні системи; обробка інформації